2015
DOI: 10.1002/cctc.201402989
|View full text |Cite
|
Sign up to set email alerts
|

XAS and XES Techniques Shed Light on the Dark Side of Ziegler–Natta Catalysts: Active‐Site Generation

Abstract: The local structure and the electronic properties of the active Ti sites in heterogeneous Ziegler–Natta catalysts, generated in situ by interaction of the precatalyst with different Al‐alkyl activators, were investigated by combining X‐ray absorption and valence‐to‐core X‐ray emission spectroscopy (XAS and vtc‐XES), coupled with UV/Vis, FTIR, and DFT theoretical calculations. Irrespective of the activator used, the active system was found to be a highly dispersed TiCl3‐like phase in which the Ti sites are surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 50 publications
(97 reference statements)
4
27
0
1
Order By: Relevance
“…Redox titrations concluded that the process is complex, and yields a distribution of titanium oxidation states, with residual Ti IV , and comparable amounts of Ti III and Ti II . The majority of the Ti III species are EPR silent; this behavior has been traced to the formation of aggregates . In this respect, one should recall that the reaction of TiCl 4 with alkyl–aluminum compounds in hydrocarbon solution ultimately leads to the precipitation of crystalline TiCl 3 , which is a moderately active and largely EPR‐silent heterogeneous propene polymerization catalyst .…”
Section: Typical Formulations and Performance Of Mgcl2‐supported Zn Cmentioning
confidence: 99%
“…Redox titrations concluded that the process is complex, and yields a distribution of titanium oxidation states, with residual Ti IV , and comparable amounts of Ti III and Ti II . The majority of the Ti III species are EPR silent; this behavior has been traced to the formation of aggregates . In this respect, one should recall that the reaction of TiCl 4 with alkyl–aluminum compounds in hydrocarbon solution ultimately leads to the precipitation of crystalline TiCl 3 , which is a moderately active and largely EPR‐silent heterogeneous propene polymerization catalyst .…”
Section: Typical Formulations and Performance Of Mgcl2‐supported Zn Cmentioning
confidence: 99%
“…5,7,8,[29][30][31] In our previous works we have demonstrated the potential of a multi-technique approach in unraveling the nature of the active TiCl x phase in catalysts obtained by reacting together titanium and magnesium chloride tetrahydrofuranate precursors and the aluminum-alkyl activator. 7,8 The investigation is more complex when the TiCl x and MgCl x phases are simultaneously supported on dehydroxylated silica in presence of tetrahydrofuran. This catalyst was developed in the 1980s by a group of scientists from Union Carbide Corporation in order to be used in the UNIPOL process to produce high density polyethylene.…”
Section: Introductionmentioning
confidence: 99%
“…Zu ihren Forschungsinteressen gehören die Eigenschaften von Oxiden, Zeolithen und Metall‐organischen Gerüstverbindungen. In ChemSusChem hat sie aminfunktionalisierte Metall‐organische Gerüstverbindungen mit gemischten Liganden und in ChemCatChem aktive Ti‐Zentren in heterogenen Ziegler‐Natta‐Katalysatoren beschrieben …”
Section: Vorgestellt …unclassified